Education and society in the Commonwealth Caribbean (Institute of Social and Economic Research, UWI, 1991)
This volume is the product of a seminar sponsored by the Research Institute for the Study of Man and the Faculty of Education of the University of the West Indies held at the Mona Campus on April 14 and 15, 1989. This seminar invited practicing policy makers and education officials from a few non-campus countries, including Grenada, to review the state of education, policy, and practice in their countries. This volume brings together the papers that were presented at the seminar. The appendices provide statistical data on the school systems in Barbados, Grenada, Jamaica, St. Kitts and Nevis, and Trinidad and Tobago
Keywords: Sociology of education